“It's the First Barrier” – Lack of Common Language a Major Obstacle When Accessing/Providing Healthcare Services Across Europe - Samkange-Zeeb, Florence; Samerski, Silja; Doos, Lucy; Humphris, Rachel; Padilla, Beatriz; Bradby, Hannah (Frontiers in Sociology, 2020)
International migration is shaping and changing urban areas as well as impacting on healthcare access and provision. To investigate how residents of superdiverse neighborhoods put together their healthcare, we conducted qualitative interviews with 76 healthcare providers and 160 residents in four European cities - Bremen, Germany; Birmingham, UK; Lisbon, Portugal and Uppsala, Sweden, between September 2015 and April 2017. A common theme arising from the data was language and communication obstacles, with both healthcare providers and users experiencing language difficulties, despite all four countries having interpretation policies or guidelines to address language barriers in healthcare. Official interpreter services were said to be unreliable and sometimes of poor quality, leading to a reliance on informal interpretation. Some coping strategies used by both service providers and users led to successful communication despite the lack of a common language. Where communication failed, this led to feelings of dissatisfaction and frustration among both users and providers. The fact that language difficulties came up across all participating countries even though this was not the main focus of the project highlights the widespread nature of language barriers and the need to address them in order to promote equal accessibility to good quality healthcare.